Effect of dietary supplementation of rice dried distillers' grain on nutrient utilization and blood biochemical profile in Osmanabadi kids - SINGH, SUKHVEER; DUBEY, MEENU; PRUSTY, SONALI; GADPAYLE, RAJKUMAR; DONERIA, RAINA (The Indian Journal of Animal Sciences, 2021)
A study on 15 Osmanabadi kids (4-5 months old) was conducted for 90 days to find out the effect of dietary inclusion of rice dried distillers grain with solubles (RDGS) on growth performance, nutrient utilization and blood biochemical parameters. They were divided randomly into 3 groups T1, T2 and T3. In the concentrate mixture, RDGS was included at 0% (T1), 10% (T2) and 20% (T3) levels replacing soybean meal. There was higher average daily gain in T3 compared to control (T1), however, the variation was non-significant up to 75 days. During last fortnight (75-90 d) the ADG was significantly higher in group T3 than T1. There was no significant effect of dietary inclusion of RDGS on percentage DMI and digestibility of nutrients, however from 75 to 90 days, DMI (kg/W0.75) was significantly (P